Effects of glycopyrrolate and atropine for oral secretions and perioperative hemodynamics in children undergoing tonsillectomy and adenoidectomy: a prospective, single-center, randomized, double-blind, controlled trial - Tao, Yi-Bin; Tang, Zi-Li; Lin, Zhong-Lan; Lei, Wei-Ping; Lu, Xin-Lei; Sun, Jian-Liang (Frontiers in Pharmacology, 2024)
Glycopyrrolate is commonly researched as a preoperative medication or in conjunction with cholinesterase inhibitors to counteract the lingering muscarinic effects of non-depolarizing muscarinic agents. However, studies have yielded inconsistent results regarding the superiority of glycopyrrolate over other anti-cholinergic drugs, such as atropine, particularly its effect on heart rate, blood pressure (BP), and glandular secretions. This study aimed to evaluate the differences in perioperative oral secretions, hemodynamics, and recovery quality with glycopyrrolate versus those with atropine before anesthesia induction in children undergoing tonsillectomy and adenoidectomy.In this prospective, single-center, randomized, double-blind, controlled trial, a total of 103 children were randomly assigned to group A (n = 51, glycopyrrolate 0.005 mg/kg) or B (n = 52, atropine 0.01 mg/kg). The follow-up anesthetic induction and maintenance protocols were the same in both groups. Vital signs, duration of surgery, extubation time, degree of wetness around the vocal cords during tracheal intubation, weight of oral secretions, and perioperative complications were recorded.Results: No significant differences were observed in the degree of wetness around the vocal cords during tracheal intubation, as well as in the weight of oral secretions, duration of surgery, or extubation time, between the two groups. The intraoperative and postoperative heart rates were lower in group A than in group B (110.